COMET – Communication for European Training Managers - Fazekas, Dora; Veloso, Bárbara (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
The adult educational and learning systems occupy a complex and important role in terms of socio-economic growth, ative citizenship and social responsibility. In this sense, effective internal and external communication processes of training organisations are considered fundamental as they contribute to the development of innovative learning products and services and to the increase of their attractiveness for potential beneficiaries. The communication in this setor is carried out internally, between the various staff members within a training organisation, and externally, between the training organisation and other stakeholders at various levels, as well as the adult learners. Sociedade Portuguesa de Inovação is a partner in the COMET – Communication for European Training Managers project, co-funded by the EC under the Life-long Learning Programme (www.spi.pt/comet). The project, based on the above assumptions, aims to strengthen the Lifelong Learning Organizations by helping managers to gain ownership of a set of communication tools to be applied for reaching personal, company and community goals through the development of a training programme for them. The project activities include: (a) Training needs analysis of the project target group; (b) Design of training curriculum, training materials and didactical methodology for the COMET training course; (c) Testing of the training course in Italy and in Portugal; (d) Quality and evaluation plan; (e) Dissemination Plan; e (f) Delivering of two final Training Courses in Italy and in Portugal.